2021
DOI: 10.1177/1742395320983871
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the management of people with heart failure with preserved ejection fraction (HFpEF) in primary care: A qualitative study of general practitioner perspectives

Abstract: Objectives To explore the perspectives of general practitioners (GPs) on the identification and management of people, including those from ethnic minority groups, with Heart Failure with Preserved Ejection Fraction (HFpEF). Methods Qualitative study. Semi-structured, face-to-face or telephone interviews and focus groups were conducted with 35 GPs in England, which were audio-recorded and transcribed verbatim. Framework analysis was used to manage and interpret data. Results Themes presented reflect four inter-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Interviews were conducted by three researchers (FF, MH, ES) who had established rapport with the interviewees through prior studies. (10)(11)(12) The same researchers familiarised, categorised and collated data into descriptive codes in an inductive approach; 50% of all interviews were double coded. All authors contributed to searching, reviewing and defining themes.…”
Section: Approachmentioning
confidence: 99%
“…Interviews were conducted by three researchers (FF, MH, ES) who had established rapport with the interviewees through prior studies. (10)(11)(12) The same researchers familiarised, categorised and collated data into descriptive codes in an inductive approach; 50% of all interviews were double coded. All authors contributed to searching, reviewing and defining themes.…”
Section: Approachmentioning
confidence: 99%
“…Cuthbert and colleagues 25 and our own research have shown that the proportion of patients included on a typical practice HF register is much lower than expected based on epidemiological data 26 and that these patients are more likely to have HFrEF 27 . Secondly, our qualitative work has demonstrated low awareness of HFpEF in primary care 9,28 . Lastly, there is variable access to HF specialist services for non‐HFrEF referrals to obtain a definitive diagnosis 7–9 …”
Section: Discussionmentioning
confidence: 84%
“…27 Secondly, our qualitative work has demonstrated low awareness of HFpEF in primary care. 9 , 28 Lastly, there is variable access to HF specialist services for non‐HFrEF referrals to obtain a definitive diagnosis. 7 , 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of HFpEF is challenging particularly at the early stage of the disease where symptoms are nonspecific and can be caused by numerous non-cardiac conditions. 11 HFpEF is less well understood than HFrEF, with greater diagnostic difficulty and management uncertainty. 9 This is where to start using other diagnostic tools for the patient with the high-risk factor such as echocardiography, exercise stress testing, and coronary angiography.…”
Section: Discussionmentioning
confidence: 99%